Determination of Furosemide and Zonisamide as a Drug Substance and in Dosage Form by Ion Pair - Reversed Phase Liquid Chromatographic Technique - B. Udaykumar Rao, Anna Pratima Nikalje (Journal of Applied Pharmaceutical Science)
An isocratic, selective, and accurate Ion pair - reversed phase liquid chromatographic method of analysis of Furosemide and Zonisamide both as a bulk drug and formulations was developed and validated. An ODS chromatographic column (250mmx4.6mm, 5Âµm) was used for the separation. The mobile phase consisted of a mixture of methanol and Tetrabutyl ammonium hydrogen sulphate (TBHS) 0.035 molar aqueous solution, pH adjusted to 6.0 using 1 N sodium hydroxide solution. The composition of TBHS with methanol used for Furosemide was 40:60(v/v) and that for Zonisamide was 50:50(v/v) delivered at a flow rate of 1.0ml/min and detection at wave length 240 nm. The developed method was validated in terms of selectivity, Linearity, limit of quantitation, precision, accuracy and solution stability. The proposed LC method achieved satisfactory resolution between Furosemide and 4-Chloro-5-sulphamoyl salicylic acid (CSSA), Zonisamide and CSSA an intermediate product possibly present in Furosemide and Zonisamide. The method can be employed as stability indicating method for both the drugs furosemide and zonisamide and its dosage form.
Keywords: Ion pair,Reversed phase,Zonisamide,Furosemide.